Pengaruh Pemanfaatan Aplikasi Mobile JKN terhadap Minat Berkunjung Pasien BPJS Rawat Jalan di Rumah Sakit Umum Astrini Wonogiri - Cahya Aninda; Indra Hastuti; Esti Dwi Rahmawati (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
This study aims to examine the effect of Mobile JKN application utilization on the outpatient visit interest of BPJS Health patients at Rumah Sakit Umum Astrini Wonogiri. The study is motivated by a hospital policy requiring outpatient BPJS patients to register through the Mobile JKN application since March 2026, which raises questions about how patients' actual use of the application relates to their interest in visiting the hospital. A quantitative survey approach was used, with data collected from 100 respondents selected through accidental sampling from a population of approximately 5,000 monthly outpatient visits, using a Likert-scale questionnaire. Data were analyzed using simple linear regression, processed with SPSS version 26. The instrument was proven valid and reliable, and the regression model satisfied all classical assumption tests. The results show that Mobile JKN utilization has a positive and significant partial effect on patients' visit interest (t = 12.362; p = 0.000), so the hypothesis is accepted. These findings suggest that improving the accessibility and usability of Mobile JKN, particularly the initial access experience, can strengthen patients' motivation to seek outpatient care, offering practical direction for hospital management to prioritize digital service enhancement.